The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.20944/preprints202203.0066.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meaningful Test & Evaluation of Indoor Localization Systems in Semi-Controlled Environments

Abstract: Despite their enormous potential the use of Indoor Localization Systems (ILS) remains 1 seldom. One reason is the lack of market transparency and stakeholders’ trust in the systems’ 2 performance as a consequence of insufficient use of Test and Evaluation (T&E) methodologies. The 3 heterogeneous nature of ILS, their influences, and their applications pose various challenges for 4 the design of a methodology that provides meaningful results. Methodologies for building-wide 5 testing exist, but their use… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The authors defined the various data that must be managed, and also created a flow of smart contracts involving various parties ranging from aircraft technicians, airlines, component manufacturers, to MRO service providers [33]. A similar proposal was also presented by Schyga et al by defining more parties including regulator, and in more detail explaining its implementation using the Hyperledger Fabric platform [34].…”
Section: Related Workmentioning
confidence: 99%
“…The authors defined the various data that must be managed, and also created a flow of smart contracts involving various parties ranging from aircraft technicians, airlines, component manufacturers, to MRO service providers [33]. A similar proposal was also presented by Schyga et al by defining more parties including regulator, and in more detail explaining its implementation using the Hyperledger Fabric platform [34].…”
Section: Related Workmentioning
confidence: 99%
“…The authors defined the various data that must be managed, and also created a flow of smart contracts involving various parties ranging from aircraft technicians, airlines, component manufacturers, to MRO service providers [30]. A similar proposal was also presented by Schyga et al by defining more parties including regulator, and in more detail explaining its implementation using the Hyperledger Fabric platform [31].…”
Section: Of 21mentioning
confidence: 99%
“…Then Schyga et al [21] showed a prototype system based on Hyperledger, which could create a Permission Blockchain System (PBS) for aircraft maintenance, repair and overhaul. Ho et al [22] proposed a similar blockchain-based system for aircraft maintenance, similar to [21]. Their system focused on parts' traceability and trackability for the inventory management.…”
Section: Introductionmentioning
confidence: 99%